(untitled) (Islamic Sciences Journal, 2024)
This study deals with one of the most important aspect of the rulings of the Qur’an with Imam Abi al-Laith al-Samarkandi, as it is a modest attempt aimed at informing his views through his approach to the verses of the rulings of the Qur’an in the interpretation of (Bahr al-Ulum).So, he, may Allah have mercy on him, was one of the ancient interpreters, and a pioneer of the science of interpretation. He was the sign of his era, the reference in the doctrine, and he had qualitative contributions to the legal sciences. The imam lived at a time when the Islamic world, from a scientific point of view, reached its climax, and the building blocks of the blogging and authoring movement in the sciences became lofty in that era. He was born in the city of Samarkand in the year (300 AH) with a difference between the books of biographies, and he grew up in an ancient family with a scientific honor and a social prestige. Al-Samarqandi was an interpreter and a jurist, and he had a long experience in various arts, and people of knowledge praised him as the best evidence . He probably died in the year (375 AH), as mentioned by Al-Dhahabi in the book (Al-Seer). Our research is an introductory chapter on the life of the author drawn from my doctoral dissertation entitled (The opinions of Imam Abi al-Laith al-Samarqandi on the interpretation of the verses of rulings in his interpretation - Bahr al-Uloom - a comparative study). This chapter is composed of three topics, the first is a statement of the aspects of life in his era in terms of political, social, intellectual and scientific cases in two demands. The second topic deals with the biography and social life of Samarkandi in eight demands including the interpretation of the tradition, in which he collected what he could of the sayings of the companions and followers, and the opinions of the imams of the predecessors from the previous interpreters.